Carbon K-shell photoionization of fixed-in-space C2H4 - Osipov, T.; Stener, M.; Belkacem, A.; Schöffler, M.; Weber, Th.; Schmidt, L.; Landers, A.; Prior, M. H.; Dörner, R.; Cocke, C. L. (My University, 2010)
Measurements of the photoelectron angular distributions in the body-fixed frame (MFPAD) have been carried out for 290- to 320-eV photons (just above the carbon K-shell ionization threshold) on C2H4 using an approach based on cold-target recoil-ion momentum spectroscopy (COLTRIMS). The results are compared with a theoretical calculation and excellent agreement is found. A direct verification of the “f-wave shape resonance” is accomplished by obtaining the complex amplitude of the l=3 partial wave, which shows a peak in its absolute value and a relative phase change of π as the energy is scanned across the resonance.